NOTCH2 negatively regulates metastasis and epithelial-Mesenchymal transition via TRAF6/AKT in nasopharyngeal carcinoma - You Zou; Rui Yang; Mao-Ling Huang; Yong-Gang Kong; Jian-Fei Sheng; Ze-Zhang Tao; Ling Gao; Shi-Ming Chen (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Clinically, distant metastasis after primary treatment remains a key problem in nasopharyngeal carcinoma (NPC). Thus, identification of the underlying mechanisms and development of novel therapeutic strategies are urgently needed. NOTCH has been shown to function as a tumor promotor that enhances angiogenesis, cancer invasion and metastasis in NPC. However, the precise roles of the four individual NOTCH receptors and their mechanisms of action are unclear. Methods We used Western blot analysis, immunofluorescence, immunohistochemical analysis, phalloidin staining, mouse tumor metastatic dissemination models, gene set enrichment analysis, immunoprecipitation assays and a series of functional assays to determine the potential role of NOTCH2 in regulating NPC metastasis. Results NOTCH2 expression in the NPC tissues of patients with cervical lymph node metastasis was lower than that of patients without cervical lymph node metastasis. Correspondingly, NOTCH2 expression was low in metastatic and poorly differentiated NPC cells. NOTCH2 expression correlated negatively with survival time in patients with NPC. Suppression of NOTCH2 expression promoted NPC cell metastasis, whereas NOTCH2 overexpression inhibited this process. Furthermore, NOTCH2 attenuated the TRAF6–AKT signaling axis via an interaction between the NOTCH2 intracellular domain (N2ICD) and TRAF6, which inhibited epithelial–mesenchymal transition (EMT) and eventually suppressed NPC metastasis. Conclusions These findings reveal that loss of NOTCH2 activates the TRAF6/AKT axis and promotes metastasis in NPC, suggesting that NOTCH2 may represent a therapeutic target for the treatment of NPC.